Expanding the Therapeutic Window of EGFR-Targeted PE24 Immunotoxin for EGFR-Overexpressing Cancers by Tailoring the EGFR Binding Affinity - Jun, Sei Yong; Kim, Dae Seong; Kim, Yong Sung (International Journal of Molecular Sciences, 2022)
Immunotoxins (ITs), which are toxin-fused tumor antigen-specific antibody chimeric proteins, have been developed to selectively kill targeted cancer cells. The epidermal growth factor receptor (EGFR) is an attractive target for the development of anti-EGFR ITs against solid tumors due to its overexpression on the cell surface of various solid tumors. However, the low basal level expression of EGFR in normal tissue cells can cause undesirable on-target/off-tumor toxicity and reduce the therapeutic window of anti-EGFR ITs. Here, based on an anti-EGFR monobody with cross-reactivity to both human and murine EGFR, we developed a strategy to tailor the anti-EGFR affinity of the monobody-based ITs carrying a 24-kDa fragment of Pseudomonas exotoxin A (PE24), termed ER-PE24, to distinguish tumors that overexpress EGFR from normal tissues. Five variants of ER-PE24 were generated with different EGFR affinities (KD ≈ 0.24 nM to 104 nM), showing comparable binding activity for both human and murine EGFR. ER/0.2-PE24 with the highest affinity (KD ≈ 0.24 nM) exhibited a narrow therapeutic window of 19 pM to 93 pM, whereas ER/21-PE24 with an intermediate affinity (KD ≈ 21 nM) showed a much broader therapeutic window of 73 pM to 1.5 nM in in vitro cytotoxic assays using tumor model cell lines. In EGFR-overexpressing tumor xenograft mouse models, the maximum tolerated dose (MTD) of intravenous injection of ER/21-PE24 was found to be 0.4 mg/kg, which was fourfold higher than the MTD (0.1 mg/kg) of ER/0.2-PE24. Our study provides a strategy for the development of IT targeting tumor overexpressed antigens with basal expression in broad normal tissues by tailoring tumor antigen affinities.
Keywords: Animals; Antibodies; Antigens, Neoplasm; Antineoplastic Agents; Cell Line, Tumor; ErbB Receptors; Humans; Immunotoxins; Mice; Neoplasms; affinity variants; anti-EGFR monobody; immunotoxin; on-target/off-tumor toxicity; PE24 toxin; therapeutic index; therapeutic window